APEX/SPIN: a free test platform to measure speech intelligibility. (1st February 2017) - Francart, Tom; Hofmann, Michael; Vanthornhout, Jonas; Van Deun, Lieselot; van Wieringen, Astrid; Wouters, Jan
Abstract: Objectives : Measuring speech intelligibility in quiet and noise is important in clinical practice and research. An easy-to-use free software platform for conducting speech tests is presented, called APEX/SPIN. Design : The APEX/SPIN platform allows the use of any speech material in combination with any noise. A graphical user interface provides control over a large range of parameters, such as number of loudspeakers, signal-to-noise ratio and parameters of the procedure. An easy-to-use graphical interface is provided for calibration and storage of calibration values. To validate the platform, perception of words in quiet and sentences in noise were measured both with APEX/SPIN and with an audiometer and CD player, which is a conventional setup in current clinical practice. Study sample : Five normal-hearing listeners participated in the experimental evaluation. Results : Speech perception results were similar for the APEX/SPIN platform and conventional procedures. Conclusions : APEX/SPIN is a freely available and open source platform that allows the administration of all kinds of custom speech perception tests and procedures.